Effect of gluten-free diet on autoimmune thyroiditis progression in patients with no symptoms or histology of celiac disease: a meta-analysis - Piticchio, Tommaso; Frasca, Francesco; Malandrino, Pasqualino; Trimboli, Pierpaolo; Carrubba, Nunzia; Tumminia, Andrea; Vinciguerra, Federica; Frittitta, Lucia (Frontiers in Endocrinology, 2023)
Background Hashimoto’s thyroiditis (HT) is the most common autoimmune disease. HT may be associated with nonthyroidal autoimmune diseases, including celiac disease (CD) or other gluten-related conditions (GRC). In the last years, interest about gluten-free diet (GFD) has increased for its supposed extraintestinal anti-inflammatory effect; thus, many patients with HT initiate GFD on their own. Objectives The aim of this meta-analysis is to examine all available data in literature about the effect of a GFD on TgAb, TPOAb, TSH, FT4, and FT3 levels in patients with HT and no symptoms or histology of CD. Methods The study was conducted according to MOOSE (Meta-analysis Of Observational Studies in Epidemiology). The search was performed on databases PubMed and Scopus. The last search was performed on 7 February 2023. Quality assessment was performed. Meta-analyses were performed using the random-effect model. Hedges’ g was used to measure the effect size (ES). Statistical analyses were performed using StataSE 17. Results The online search retrieved 409 articles, and 4 studies with a total of 87 patients were finally included for quantitative analysis. The risk of bias was generally low. The mean period of GFD was almost 6 months. The meta-analyses showed reduction in antibody levels with ES: −0.39 for TgAb (95% CI: −0.81 to +0.02; p = 0.06; I² = 46.98%) and −0.40 for TPOAb (95% CI: −0.82 to +0.03; p = 0.07; I² = 47.58%). TSH showed a reduction with ES: −0.35 (95% CI: −0.64 to −0.05; p = 0.02; I² = 0%) and FT4 showed an increase with ES: +0.35% (95% CI: 0.06 to 0.64; p = 0.02; I² = 0%). FT3 did not display variations (ES: 0.05; 95% CI: −0.38 to +0.48; p = 0.82; I² = 51%). The heterogeneity of TgAb, TPOAb, and FT3 data was solved performing sub-analyses between patients with or without GRC (TgAb p = 0.02; TPOAb p = 0.02; FT3 p = 0.04) and only for FT3, performing a sub-analysis between patients taking and not taking LT4 (p = 0.03). Conclusion This is the first meta-analysis investigating the effect of GFD on HT. Our results seem to indicate a positive effect of the gluten deprivation on thyroid function and its inflammation, particularly in patients with HT and GRC. However, current lines of evidence are not yet sufficient to recommend this dietary approach to all patients with a diagnosis of HT.